2021
DOI: 10.47654/v25y2021i3p46-57
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Web-Based Audio-Visual Media Applications in Monitoring Children’s Growth to Prevent Stunting

Abstract: In this study, we explore comparing mothers’ knowledge of health education conducted through web-based audio-visual media between the intervention group and the control group who only read books on maternal and child health. This study employed criteria for the respondents: mothers who have toddlers, both in the control and treatment groups. The respondents were asked to fill out a questionnaire ( post-test). Meanwhile, for the control group, after the pre-test, the respondents read a book on maternal and chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…Additionally, the use of short videos within the didactic process may be an innovative learning strategy and an important parameter for understanding a subject, while the application of differentiated teaching confirmed the new audiovisual theory in education that suggests it as an audiovisual technology-supported teaching methodology [4]. Despite what the most recent research has shown about how vital the formation of the positive use of short videos [116,120,121,270] and the effective application of differentiated teaching [159,[271][272][273][274] in teaching-learning procedure for learner achievement, the specific fields are still fluid, and more research on them is needed. In closing, a final inference that arises from the employment of the specific ICTs through a lesson plan is that it indicates how important its effective integration in the teaching-learning procedure as well as their immediate institutionalization within the framework of the didactic process for an effective education is.…”
Section: Concluding Discussionmentioning
confidence: 85%
“…Additionally, the use of short videos within the didactic process may be an innovative learning strategy and an important parameter for understanding a subject, while the application of differentiated teaching confirmed the new audiovisual theory in education that suggests it as an audiovisual technology-supported teaching methodology [4]. Despite what the most recent research has shown about how vital the formation of the positive use of short videos [116,120,121,270] and the effective application of differentiated teaching [159,[271][272][273][274] in teaching-learning procedure for learner achievement, the specific fields are still fluid, and more research on them is needed. In closing, a final inference that arises from the employment of the specific ICTs through a lesson plan is that it indicates how important its effective integration in the teaching-learning procedure as well as their immediate institutionalization within the framework of the didactic process for an effective education is.…”
Section: Concluding Discussionmentioning
confidence: 85%
“…Pola asuh yang tidak adekuat dan pengetahuan orang menjadi tema utama penyebab stunting pada bayi bawah dua tahun (baduta) di Kabupaten Klaten, mulai dari awal kelahiran sampai dengan anak berusia 2 tahun. Pola asuh yang dimaksud adalah pola asuh yang telah ditetapkan oleh UNICEF pada model The Ekstended Model of Care, yaitu sebuah model yang menjelaskan bahwa determinan pola asuh dimulai dari perhatian atau dukungan orang tua terhadap anak, pemberian ASI atau makanan pendamping pada anak, rangsangan psikososial, persiapan dan penyimpanan makanan, praktik kebersihan danhygiene sanitasi lingkungan, serta perawatan balita dalam keadaan sakit (23).…”
Section: Pendahuluanunclassified
“…In article two (Widowati et al, 2021) audiovisual media that presents knowledge and daily real-life experiences will be more easily accepted by mothers so that they can quickly increase their knowledge and understanding. Article five (Ernawati et al, 2021) states that web-based education using smartphones is a more interesting audiovisual presentation and can be played over and over again to make it easier to understand. Researchers believe that health education through webbased audiovisual media to the public, especially parents, can be the right alternative choice in preventing stunting.…”
Section: Nutrition Education Mediamentioning
confidence: 99%
“…In the second article (Widowati et al, 2021) the provision of health education through video media on motherl knowledge about balanced nutrition in toddlers. Based on the results of research in article five (Ernawati et al, 2021) it can be concluded that public health education through audiovisual media consisting of videos about toddler growth and development and web-based stunting can effectively improve parents' knowledge about monitoring the growth and development of toddlers.…”
Section: B Types Of Educational Mediamentioning
confidence: 99%
See 1 more Smart Citation